P-164 Using virtual reality in patients with palliative care needs. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Wright, Cecily; Babber, Adarsh; Price, Sophie
Abstract : Background: Virtual Reality (VR) is a 360° audio-visual simulation presented as reality to the user, allowing immersion and distraction from symptoms or treatments. There is some evidence based support for the use of VR technology to reduce symptoms including pain, anxiety and stress in patients with cancer, chronic pain and other conditions (Li, Montaño, Chen & Gold, 2011; Gorini, Pallavicini, Algeri, Repetto et al ., 2010; Oyama, 1998). The feasibility and impact of this technology was assessed in a hospice setting. Method: A pilot project for use of VR technology took place in a hospice inpatient and day unit over a four week period. Patients were assisted to use the technology by trained staff, with each session lasting approximately seven minutes. Patients chose their own 'experience' from a selection of options. A follow-up questionnaire on the experience, self-reported symptoms and any change in symptoms was completed by each patient. Results: A total of 14 sessions took place and each participant completed a questionnaire. All of the patients agreed they would use VR again and would recommend it to others. 75% of patients who reported pain felt they experienced some improvement following the session. Similarly, 50% of patients reporting breathlessness and 81% expressing anxiety, believed they improved. Comments were generally positive, themed around 'immersion' and 'escapism'. The results were limited by the small number of participants and self-reported effect, but showed an overall improvement in symptoms. Discussion: This pilot study demonstrated VR technology to be a beneficial and well tolerated means of providing immersion and distraction therapy. Use was limited by the resources needed for the equipment, including cost, programmes available and trained staff. However, with rapidly emerging new technology and positive user feedback, VR is a viable non-invasive means for symptom management in palliative care.